Religious Coping of Farming Communities in Dealing with COVID-19 Pandemic in Pakkabba Village, Takalar District - Sahabuddin, Jumadi; Salim, Nurlela; Rahman, Abdul (KnE Social Sciences, 2024)
In late December 2019, the global population was shocked by the discovery of the coronavirus originating in Wuhan Province, China. On February 12, 2020, the World Health Organization (WHO) declared the virus highly deadly and named it coronavirus 2019. The virus rapidly spreads to various parts of the world. It is almost certain that the outbreak has affected every country, including Indonesia. The Indonesian government subsequently declared the COVID-19 outbreak a national disaster. To ensure life safety and curb the spread of COVID-19, a policy was implemented, limiting the movement and activities of people outside their homes. This decision was based on considerations from various parties, particularly health experts and scholars. This policy certainly has an impact on the economic activities of the community, including those in rural areas. Research conducted in Pakkabba Village revealed that restrictions on activities outside the home led to decreased incomes and economic challenges. However, the community’s strong optimism to make a living can overcome these difficulties. Facing COVID-19 involves adhering to health protocols and strengthening solidarity through mutual assistance to alleviate the economic burden. In addition, a religious approach (religious coping) was also carried out in fostering work spirit despite being in a COVID-19 situation. Keywords: COVID-19, religious coping, social solidarity, optimism